Discussion on Redesign of Image from Digital Printing Process (Asian Journal of Social Science Studies, 2017)
Digital printing is an indispensable link in the modern printing technology. It is the traditional pre-press process on the transition to digital technology in imaging technology, the digital printing technology. Digital printing expounds digital image process in the design means and methods and their influences on the printing quality from the angle of separation method, image processing method, etc..